2013
DOI: 10.2166/wst.2013.251
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of climate change on rainfall extremes and urban drainage systems: a review

Abstract: A review is made of current methods for assessing future changes in urban rainfall extremes and their effects on urban drainage systems, due to anthropogenic-induced climate change. The review concludes that in spite of significant advances there are still many limitations in our understanding of how to describe precipitation patterns in a changing climate in order to design and operate urban drainage infrastructure. Climate change may well be the driver that ensures that changes in urban drainage paradigms ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
142
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(148 citation statements)
references
References 83 publications
3
142
0
3
Order By: Relevance
“…However, our investigation focused on rivers, not on the small-scale flooding caused by changes in intense local precipitation, which may have a greater impact in the future (e.g., in urban areas) (Arnbjerg-Nielsen et al, 2013;Olsson and Foster, 2014). We found a small, albeit not statistically significant, negative trend in river high flow, indicating a 0.4 % decrease in 10-year flood frequency each decade.…”
Section: Changes In High Flows In Swedenmentioning
confidence: 74%
“…However, our investigation focused on rivers, not on the small-scale flooding caused by changes in intense local precipitation, which may have a greater impact in the future (e.g., in urban areas) (Arnbjerg-Nielsen et al, 2013;Olsson and Foster, 2014). We found a small, albeit not statistically significant, negative trend in river high flow, indicating a 0.4 % decrease in 10-year flood frequency each decade.…”
Section: Changes In High Flows In Swedenmentioning
confidence: 74%
“…Moreover, temporal scales relevant to flood risk vary enormously with area (Blöschl and Sivapalan, 1995;Westra et al, 2014): for catchments, hours to days are relevant (Mueller and Pfister, 2011), whereas urban drainage systems of ∼ 10 km (Arnbjerg-Nielsen et al, 2013) are impacted at timescales from minutes to hours (De Toffol et al, 2009), and soil erosion can occur at even smaller scales (Mueller and Pfister, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A recent review by Willems et al (2012a, b) and Arnbjerg-Nielsen et al (2013) of the impacts of climate change on short-duration rainfall extremes and urban drainage showed that short-duration rainfall extremes were projected to increase by 10-60 % in 2100 relative to the baseline period ). An urban drainage system may damp or amplify changes in precipitation, depending on the system characteristics.…”
Section: Urban Catchmentsmentioning
confidence: 99%